Does interindividual variation in energetic demand influence food sharing in the honeybee? - Reade, Abbie J., author; Naug, Dhruba, advisor; Florant, Gregory, committee member; Ode, Paul, committee member (Colorado State University. Libraries, 2017)
A central benefit of group living is the cooperative acquisition and sharing of resources but the costs associated with these processes set up a potential conflict between individual and group level fitness. This means that all individuals do not get an equal share of the benefits or pay an equal share of the costs, which also results in an overall decrease in the average fitness of all group members. In contrast to group living animals in which behavior is driven by considerations of individual fitness, in eusocial groups such as the honeybee colony, it is generally considered that all group members contribute equally toward group efforts with selection primarily acting at the colony level. However, one can hypothesize that if individuals differ in their intrinsic energetic requirements, this difference in the cost of self-maintenance would lead to differences in the amount of resources they can contribute to the colony pool. Using the honeybee colony as a model, I investigated this idea regarding whether differences in individual energetic requirements among eusocial group members influence the amount of food that an individual shares with the group. First I investigated whether there was interindividual variation in carbohydrate demand among foragers using a capillary feeder assay. Next I asked whether the carbohydrate demands of individual foragers were a function of their metabolic rates. Then I used a series of sharing experiments in the field and in the lab to determine whether food sharing by an individual forager was influenced by her own energetic demand. The results of my research show that even though there is substantial variation in energetic demand among the members of a honeybee colony, it does not influence the amount of food an individual shares with the colony. This suggests that either honeybee colony members indeed work in a truly "altruistic" fashion or that there are other possible implications of such differences.
Keywords: interindividual variation; nutritional geometry; social dynamics; metabolic rate; honeybee; prandiology